Hydrophobic interaction mediated coating of pluronics on mesoporous silica nanoparticle with stimuli responsiveness for cancer therapy. (14th June 2018) - Sha, Luping; Wang, Da; Mao, Yuling; Shi, Wei; Gao, Tianbin; Zhao, Qinfu; Wang, Siling
Abstract: In this research, a novel method was used to successfully stably coat Pluronic P123 on mesoporous silica nanoparticles (MSNs). Co-constructing a drug delivery system (DDS) with P123 and MSNs has not been previously reported. In this DDS, the coating of P123 was realized through a hydrophobic interaction with octadecyl chain-modified MSNs. The experiments found only Pluronic with an appropriate ratio of hydrophilic and lipophilic segments could keep the nanoassemblies stable. For comparison, nanoassemblies consisting of P123 and octadecyl chain-modified MSNs with or without a disulfide bond were prepared, which were denoted as PSMSNs and PMSNs, respectively. The disulfide bond was expected to endow the system with redox-responsiveness to enhance the therapeutic effect meanwhile decreasing the toxicity. A series of experiments including characterization of the nanoparticles, in vitro drug release, cell uptake and cellular drug release, in vitro cytotoxicity, cell migration and biodistribution of the nanoparticles were carried out. Compared with the PMSNs, PSMSNs displayed a redox-responsive drug release property not only in in vitro release text, but also on the cellular level. In addition, the cell migration experiments proved that the coating of P123 endowed the system with the ability of anti-metastasis. The accumulation of P123 in the tumor was enhanced after coating the MSNs by virtue of the 'EPR' effect of nanoparticles compared with the solution form.